2015
DOI: 10.1038/pr.2015.142
|View full text |Cite
|
Sign up to set email alerts
|

Low-glycemic index diet may improve insulin sensitivity in obese children

Abstract: ArticlesClinical Investigation nature publishing group BACKGROUND: A low-glycemic index (GI) diet may be beneficial for weight management due to its effect on insulin metabolism and satiety. METHODS: Obese children aged 9-16 y were randomly assigned either a low-GI diet or a low-fat diet (control group) for 6 mo. Body composition changes were measured by dualenergy X-ray absorptiometry and bioelectrical impedance analysis. Insulin sensitivity was measured by fasting plasma glucose and insulin. RESULTS: Fifty-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 31 publications
(41 reference statements)
2
53
0
6
Order By: Relevance
“…In total, 68 studies reported metabolic measures and details of these are listed in Table , alongside the outcome(s) of interest from each study. While various glucose measures were reported, we focused on fasting‐glucose measurements for this article (56 studies), as fasting glucose is used clinically to identify prediabetes and diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 68 studies reported metabolic measures and details of these are listed in Table , alongside the outcome(s) of interest from each study. While various glucose measures were reported, we focused on fasting‐glucose measurements for this article (56 studies), as fasting glucose is used clinically to identify prediabetes and diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…These articles were then subjected to inclusion or exclusion by application of the full‐text inclusion criteria. We included 109 study arms from 101 individual articles (Table ) . Studies varied in length from 1 week to 104 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…A2(C)). Including the control subset in Visuthranukul et al 109 (n = 104) did not impact this result, in that it was still impossible to find a change of BMI-SDS, among the range of changes seen, that would ensure an improvement in mean HDL (Appendix Fig. A2(B)).…”
Section: Quantitative Analysismentioning
confidence: 92%